Voting from prison: against the democratic case for disenfranchisement. Issue 3 (30th November 2018) - Marshall, Pablo
ABSTRACT: This article critically analyses and discards two democratically justified cases for the disenfranchisement of prisoners. These cases are offered in relatively recent published works by Peter Ramsay and Claudio López-Guerra, which – unlike other approaches – take the democratic challenge to disenfranchisement very seriously. Their arguments are based on a diagnostic of the conditions of imprisonment, which concludes that prisoners' electoral participation is problematic for democracy because it endangers electoral integrity. This article argues against their positions and suggests that for prisoners to be treated as democratic citizens they must be recognized as electors and given an opportunity to vote. Firstly, it will be affirmed that prisoners cannot be made responsible for the conditions of their imprisonment and that prisons must adequately meet democratic requirements. It will also be affirmed that, if these requirements were fulfilled, the conditions of prisoners in a democratic prison would not be sufficiently different, in relevant aspects, from the conditions of other enfranchised people. Secondly, it will be asserted that, at least at to some extent, their arguments underestimate the possibilities of prison reform and electoral regulation to overcome the democratic problems of coercion and manipulation, which they target as two main problems of enfranchisement.